Hand hygiene practices among doctors in health facility in a semi-urban setting - Ibrahim Aliyu; Teslim O Lawal; Wasiu Olawale; Kehinde Fasasi Monsudi; Bashir Mariat Zubayr (BLDE University Journal of Health Sciences, 2018)
INTRODUCTION: Hand hygiene is an integral part of personal hygiene; poor hand hygiene practice may result not only in self-hurt but also may serve as a vehicle for transmission of infection among patients. Hence, knowledge of proper hand hygiene practice will significantly reduce the burden of infectious diseases. MATERIALS AND METHODS: This was a cross-sectional study involving doctors at Federal Medical Centre Birnin Kebbi; it was conducted from September 2015 to November 2015. Convenience sampling method was adopted. Pretested self-administered questionnaire based was used; relevant information such as age, sex, profession, years of working experience, awareness of Global HandWashing Day, hand-washing technique, steps in hand washing, ability to list the five moments in hand washing, and principles of hand washing were obtained. RESULTS: There were 33 males and 12 females with a male to female ratio of 2.8:1. All respondents believed hand washing reduces the risk of transmitting or contracting infections. Soap and water was the most common agent for hand cleansing, majority of the respondents (86.7%) had been taught on the technique of hand washing; however, only 19 (42.2%) of them wash their hands before examining patients; but all the respondents (100%) wash their hands after examining patient or handling their secretions; similarly, they all reported washing their hands after using the restroom. Almost all of the respondents (97.8%) use water and soap for hand washing. Furthermore, only 44.4% of the respondents had their personal hand rub. CONCLUSION: Soap and water was the most common agent for hand cleansing, and there was poor utilization of hand rub; and most respondents did not wash their hands before patient contact.